Diversity of universal stress protein in Enterobacteriales and its reduced expressions on Pectobacterium brasiliense after manuka honey treatment - CHOTIMAH CHOTIMAH; ALAN SOFFAN; TRI JOKO (Society for Indonesian Biodiversity, 2024)
Abstract. Chotimah, Soffan A, Joko T. 2024. Diversity of universal stress protein in Enterobacteriales and its reduced expressions on Pectobacterium brasiliense after manuka honey treatment. Biodiversitas 25: 49-52. Universal stress proteins (Usps) support the survival of an organism by increasing their expressions under stress conditions, which include nutritional deficiencies, heat shock, and antibiotics. However, the expression of uspA in Staphylococcus aureus decreased after manuka honey exposure. Manuka honey also inhibits the growth of Pectobacterium brasiliense, although its effect on the usp gene of this soft-rot pathogen has never been studied. This study aimed to determine the diversity of Usps in P. brasiliense and their orthologs from Enterobacteriales using phylogenetic analysis. The effects of manuka honey on usp gene expressions were also investigated using quantitative real-time polymerase chain reaction and pathogenicity assay of P. brasiliense on Chinese cabbage. The results revealed that the UspA, UspB, and UspE of P. brasiliense had the closest similarity to those of P. carotovorum. By contrast, UspG had the closest similarity to P. polaris. The usp gene expressions were downregulated by 5, 16, 10, and 62% in 5% (w/v) manuka honey treatment. When tested on Chinese cabbage, P. brasiliense treated with manuka honey caused smaller lesion symptoms than those in the control treatment. This reduced virulence of P. brasiliense may be related to the reduced expression of usp genes triggered by manuka honey.